Good practices: experiences and challenges- Unsam, Argentina - José Barbero; Tamara Werhun Chomik; Lovisa Ericson; Daniel Alvarez (Journal of Sustainability Perspectives, 2022)
The impact of university activities on the environment should be studied and managed based on the constant evaluation of real consumption needs, on the use of reusable or recyclable resources and on the encouragement of an active and participatory role in terms of care and improvement of the environment (physical and social) through responsible use. This is a challenge that requires the commitment of the entire university and involves a continuous process of awareness-raising among students, teachers, researchers and staff. In 2016, UNSAM the National University of San Martin (Universidad Nacional de San Martín) conducted a study on mobility in its main campus "Miguelete", which covers an area of 20 hectares. Subsequently this and other works and analysis were systematized in the "Best Environmental Practices Guide" made in 2019 and approved by the Superior Council of the UNSAM. This Guide aims to provide tools to make changes in habits and new practices to minimize the impacts that the university itself generates on the environment. The objective of the proposed presentation is to share with other universities the common challenges and some actions to configure a comprehensive policy that combines and promotes economic, social and environmental sustainability within the framework of the 2030 Agenda.Keyword: Good environmental Practices/ Sustainable University Campus/Sustainable University Mobility/SDGs/Participative approach